YouTube Animated Movies as an Alternative Media to Enhance Students’ Listening Skills - Nurdiawati, Dede (LPPM Universitas Pancasakti Tegal, 2019)
These objectives of this research are to investigate whether using YouTube animated movies as an alternative media enhances students’ listening skills and to find out what attitudes the students have towards learning through YouTube animated movies as an alternative media. The participant was thirty-two students of Junior High School. The collecting data use questionnaire, observation, and interviews. The results were: (1) there were twenty-five students (78.13%) who strongly agreed that the students wanted their teachers to use more animated movies on YouTube as one of the alternative media in the classroom; (2) there were two students’ expectation of the teachers’ role in teaching and learning listening skill by using YouTube animated movies in the classroom: twenty-nine students (90.63%) who strongly agreed that the teachers became facilitators and mentors who helped students to learn when teaching and learning listening process took place in the classroom; and there were twenty-three students (71.88%) who strongly agreed that the teachers walked around the class to observe the process of the students’ work assignment; (3) More than twenty-five students agreed that YouTube animated movies could help the students in studying English especially in learning listening; and (4) It also found that majority of the students had higher and good attitude in teaching and learning listening process by using YouTube animated movies. It can be concluded that the use of YouTube animated movies can enhance students’ listening skills. Besides, it is recommended that YouTube should be considered as an effective instructional medium for enhancing the content learning of the students and as an important teaching resource in the classroom.